Geometry of homogeneous bounded domains lectures given at the Centro internazionale matematico estivo (C.I.M.E.) held in Urbino (Pesaro), Italy, July 5-13, 1967 - C.I.M.E. Summer School Urbino, Italy) (1967; Vesentini, Edoardo; Centro internazionale matematico estivo; SpringerLink (Online service). (Heidelberg, Germany Springer Berlin, 2011)
Gindikin, I.I. Pjateckii-Sapiro, E.B. Vinberg: Homogeneous Kähler manifolds.- S.G. Greenfield: Extendibility properties of real submanifolds of Cn.- W. Kaup: Holomorphische Abbildungen in Hyperbolische Räume.- A. Koranyi: Holomorphic and harmonic functions on bounded symmetric domains.- J.L. Koszul: Formes harmoniques vectorielles sur les espaces localement symétriques.- S. Murakami: Plongements holomorphes de domaines symétriques.- E.M. Stein: The analogues of Fatous?s theorem and estimates for maximal functions.
S.G. Gindikin, I.I. Pjateckii-Sapiro, E.B. Vinberg: Homogeneous Kähler manifolds -- S.G. Greenfield: Extendibility properties of real submanifolds of Cn -- W. Kaup: Holomorphische Abbildungen in Hyperbolische Räume -- A. Koranyi: Holomorphic and harmonic functions on bounded symmetric domains -- J.L. Koszul: Formes harmoniques vectorielles sur les espaces localement symétriques -- S. Murakami: Plongements holomorphes de domaines symétriques -- E.M. Stein: The analogues of Fatous?s theorem and estimates for maximal functions.
Originally published: Florence: Cremonese, 1967.
Electronic reproduction.
Keywords: Geometry, Differential -- Congresses